Pinjaman Modal Usaha Tani Pada Bank Daerah Versus Bank Negara - David Oscar Simatupang (EKONOMI & SOSIAL, 2019)
Rice Commodity is a commodity that has high economic value, so it needs to be developed by increasing loan investment, so that the important role of the Bank for lending is very important for the development of agricultural businesses and farmers' economy. This study aims to see whether there is a difference between the value of the loan, type of loan, income, and the form of loan against the selection of the type of bank. This research was conducted in Merauke Regency, Tanah Miring District, with a sample of 97 respondents from household heads of farm households. Using quantitative descriptive analysis. The results of the analysis show that state-owned banking institutions are chosen 83% higher than regional banks for consumer income, namely <1 Million, 1 Million - 3 Million, and> 3 and at 32.5%, state-owned commercial banks have a higher percentage of loans compared to Regional Owned Commercial Banks which is 83%. For the highest percentage loan scheme owned by the State-Owned Commercial Bank with 83%, namely in the KUR scheme the loan has a significant result or gets the results of a hypothesis that is rejecting Ho or accepting Ha where in taking a loan for the loan scheme has a significant relationship to the type of bank X2 Table 15,507 X2 Calculate = 18,005 with degrees of freedom (db) of 2 and a = 0.05 or 5%, with a P-Value value of 0,000 smaller than 0.05, or it can be said in state and regional public banks, credit schemes very influential in the selection of loans. %) and Agriculture (34.2%), and type Schema variables